High-throughput Phenotyping for Abiotic Stress Resilience in Cereals - Islam, Nusrat Ul; Wani, Shabir Hussain; Ali, Gowhar; Dar, Zahoor Ahmad; Wani, Altaf; Lone, Ajaz (Journal of Cereal Research, 2021)
Around 70 percent of crop yield losses are projected because of climate induced abiotic stresses like moisture stress, soil salinity and heat stress. Critical to the stability of cropping systems in the face of climate change is the capacity to rapidly grow germplasm with tolerance to complex polygenic inherited abiotic and biotic stresses combined. Molecular breeding provides the means to speed up cereal breeding, but adequate phenotyping protocols are required to ensure that the much-anticipated benefits of novel breeding tools can be realized. Tremendous advances in phenomics have taken place in the recent past. Both forward and reverse phenomics have developed to help determine either the best genotype with the desired feature or mechanism and the genes that make the genotype the best. High-throughput phenomics studies include techniques for screening substantial germplasm sets for a specific trait using high-throughput phenotyping (HTP) technologies like advanced robots, high-tech sensors, 3D imaging, fluorescence imaging, NIR imaging, lemnatec, etc. The high velocity of plant phenotyping based on phenomics accelerates the selection phase of potential advanced germplasm resilient towards climate induced stresses.